DIGESTIVITY OF BROILER CHICKEN RATE FEEDED AMINO ACID LYSINE AND METHIONINE THROUGH DRINKING WATER IN CLOSE HOUSE CAGES - P. W. K., Udayana; Astawa, I P. A.; Mahardika, I G. (Jurnal Peternakan Tropika; Vol 10 No 2 (2022): Vol. 10 No. 2 Tahun 2022; May - August, 2022)
The aim of the study was to determine the effect of giving the amino acids lysine and methionine through drinking water on dry matter digestibility, organic matter digestibility, digestibility crude protein, and crude fiber digestibility of the given ration. The research was carried out in the cage owned by Mr. I Made Arcana located in Candikusma Village, Jembrana for 32 day. The study used a completely randomized design (CRD) consisting of four treatment and four replications and in each experimental unit using 12 chickens strain CP 707. The treatment given was P0= the use of 0% lysine and methionine, P1= the use of 0.02% lysine and methionine, and P2= 0.025% lysine and methionine, and P3= the use of 0.03% lysine and methionine. The observed variables include the digestibility of the material dry matter, digestibility of organic matter, digestibility of crude protein, digestibility of crude fiber. Research result showed that administration of the amino acids lysine and methionine through drinking water can increase dry matter digestibility, crude protein digestibility, but can’t increace to crude fiber digestibility and organic matter digestibility. Keywords: broiler, amino acids, lysine and methionine, digestibility